Understanding Bullying of Adolescents with ADHD: A Narrative Inquiry - Tan, Terry (Archīum Ateneo, 2019)
Individuals with non-normative identities face stigma from society, such is the experience of adolescence diagnosed with ADHD. They have a higher risk of being bullied as their experience of social rejection tend to worsen at this stage. This study looks into the bullying narratives of adolescents with ADHD as well as their attempts at resistance. The lens of Narrative analysis and the Theory of Power and Resistance were adapted to help make sense of the stories of the participants as they talk about their personal experience of bullying. Because narratives can be used to organize thoughts and experiences, balance of power that exists between bullies and victims, remain to be dependent on the relationship between power and resistance (Foucault, 1980). Narrative interviews were done to gather data from six male adolescents who were diagnosed with ADHD and have experienced being bullied by their peers. Results present three different phases of transition from each of the participants where they revealed a journey of transitioning from a victim phase, to a realization phase, and eventually reaching a redeeming phase. Implications on the social forms of bullying and on the ability of adolescents with ADHD to hyperfocus as a way of dealing with bullying were discussed with recommended interventions.